Salvage high-dose-rate brachytherapy for prostate cancer persistence after brachytherapy: repeated use of a polyethylene glycol hydrogel spacer - Hepp, Rodrigo (J Contemp Brachytherapy, 2018)
PURPOSE: The aim of this study is to determine if a repeated hydrogel injection in a previously irradiated patient prior to salvage high-dose-rate brachytherapy (HDR-BT) is feasible. MATERIAL AND METHODS: A 61-year-old man with an organ confined (cT1c cN0 cM0, Gleason score 3 + 3 = 6, initial prostate-specific antigen [PSA] 7.9 ng/ml) prostate cancer was previously treated with HDR-BT (3 fractions of 11.5 Gy every 2(nd) week) after hydrogel injection to reduce the rectal dose. Ten months after, an isolated local persistence was seen on a PSMA PET-CT. Nadir PSA was 2.0 ng/ml, 3 months after treatment and was 3.95 ng/ml by the re-treatment. Salvage therapy consisted of HDR-BT (3 fractions of 9 Gy every 2(nd) week) with a simultaneous integrated boost to the residual region. Again, a hydrogel injection (10 ml) was applied to reduce the rectal dose prior to the treatment. RESULTS: Both hydrogel injection and salvage HDR-BT could be applied without any significant complications or toxicity. A good PSA response was observed with a nadir of 0.42 ng/ml, twelve months after salvage therapy. Acute toxicity (max grade II) resolved within 2 days after treatment. CONCLUSIONS: The use of a hydrogel prior to salvage HDR-BT in a patient previously treated with HDR-BT is feasible and could help reduce the rectal exposure in the salvage setting.